FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY ( Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) (Students' Journal of Accounting and Banking, 2014)
One of the qualitative characteristics of financial reporting was relevant, that its realization can be seen from the timeliness of reporting. Timeliness could be judging from the audit delay,which is the lenght of time from a company fiscal year end to the date of auditor’s report. The purpose of this study was to determine the influence of company size, profitability, solvency and size of public accountant to audit delay. Sampling purposive sampling technique that uses the selection of samples by certain criteria so that the sample in this research were obtained as many as 95 manufacturing company listings on IDX in 2010-2012. This research data analysis methods are descriptive analysis, the assumption of normality test, test of classical models, and test hypotheses. The results showed partial testing, showed a significant effect on the profitability of the audit delay. On the other hand, the size of the company, solvency and size of public accountant do not have any influence towards audit delay.Keywords: Audit Delay, the size of the company, profitability, solvability, size of public accountant